An assessment of the relationship between driving skills and driving behaviors among Chinese bus drivers. (January 2019) - Zhang, Zuobo; Ma, Tianshan; Ji, Nuoya; Hu, Zhe; Zhu, Wenying
To provide helpful suggestions to bus companies regarding reducing the number of bus accidents and improving public transportation safety, we further researched the relationship between driving skills and driving behaviors; bus drivers from six bus companies of the Hefei Bus Group were investigated. The reliability and validity of the Driver Behaviour Questionnaire, the Driver Skill Inventory, and 287 valid questionnaires were tested; the relationships between the Driver Behaviour Questionnaire and Driver Skill Inventory factors were explored; and their influence on traffic accidents was analyzed by structural equation modeling. Significant positive associations were found between driving experience and safety motive, whereas negative relationships were found between errors and safety motive. Safety motive has a negative effect on violations, and violations are the most important factor leading to traffic accidents. Therefore, bus companies should enhance safety education, and interventions should not only directly relate to the involvement of bus drivers in traffic accidents but also consider the role played by violations.